Mobile Apps as a Tool to Shape Transport Services and Transport Behaviour of Residents: A State of Art and Recent Developments on the Example of Poland - Grzegorz DYDKOWSKI; Anna URBANEK (Communications of International Proceedings, 2021)
Forecasts indicate further development of cities and increasing number of residents in cities. This will be related to the need of increasing the efficiency and productivity of city transport systems. Information and Communication Technologies (ICT) can increase attractiveness of urban transport systems, including public transport, they can offer information, a possibility of electronic payments, and integration of provided mobility related services. Many apps installed on mobile devices are available, in many cases these are separate applications related to travel planning and timetables, payments, but also separate ones related to the transport organisers or entities offering movements by single-track vehicles or cars in short-term rental systems. In various states and cities worldwide studies are carried out and pilot solutions implemented in the field of integration in the MaaS formula, which provides premises for such solutions implementation. However, formulae of gradual solution reaching should be considered here, the integration and MaaS development treated as a process, in which entities responsible for city transport systems, to a larger extent getting involved in the areas of service marketing and sales with the use of mobile devices, are now the leaders. Because it is not a good solution for the service users, when in many cases applications with timetables or tickets selling are not affiliated to the transport organiser, which does not declare the current nature of contained data or responsibility for their operation. The paper presents the impact of changes in ICT technologies, occurring over a dozen or so recent years, on the mobility of residents and also on the provision and accessibility of transport services. The studies utilised the analysis of solutions functionality, including applications related to mobility and transport services, available and installed on mobile devices - especially on smartphones. In particular, applications related to transport and electronic payments, available on Google Play and App Stores, were analysed.
Keywords: mobile apps; public transport; ICT; mobility